An update on frailty in lung transplantation. Issue 3 (June 2020) - Varughese, Rhea; Rozenberg, Dmitry; Singer, Lianne G.
Abstract : Purpose of review: Frailty is prevalent in lung transplant candidates, and recent studies have demonstrated associations with increased mortality before and after transplantation. This review highlights important findings on the trajectory of frailty throughout the lung transplant process and provides valuable insight into frailty and some of its modifiable elements. Recent findings: There have been several frailty indices used in lung transplantation, specifically the Frailty Phenotype, Short Physical Performance Battery (SPPB), and Cumulative Deficits. The two most commonly used measures – Frailty Phenotype and SPPB – reflect physical frailty and have been associated with increased morbidity and mortality pre and post-transplantation. However, there is emerging evidence that physical elements of frailty are reversible with rehabilitation before and after transplantation with improvement in frailty by 6 months after transplantation. The associations of frailty with physical activity levels, exercise capacity, and inflammation are discussed. Summary: Frailty is prevalent before transplant, but physical frailty is modifiable with rehabilitation and transplantation. Thus, physical frailty should not be an absolute contraindication to lung transplantation, but efforts should focus on elements of frailty that are potentially modifiable.